Red Sea Polychaetes from the Gulf of Elat (Aqaba) : a contribution to the knowledge of the Polychaeta fauna and the environmental conditions which affects its distribution - Gitay, Asher (Department of Biological Sciences, 2016)
A study of 50 samples of Polychaeta mainly from a northern profile (0.5 - 550 m) and down to 800 m, reveals that the fauna is characterised by extremely small specimens and a great taxonomic divergence. Techniques of handling minute specimens are described, together with 21 new species, including three subspecies, six new genera and a new subgenus. The discovery of aberrant genera indicates a substantial endemism, the evolution of which is enabled by: (a) the narrow Straits of Tiran which separates the Gulf from the Red Sea proper; (b) the hydrographical factors causing vertical homogeneity of temperature, salinity and oxygen, as well as (c) a possible zone of convergence which isolates the Gulf's northern part to an as yet unknown degree. The pattern of family distribution and specimen frequencies confirms the existence of six successive benthic associations along an analysed sediment profile. The poor biomass of the fauna indicates that the Gulf has an overall low productivity, caused by the limited amount of fresh water run-off, low content of organic matter and small quantities of nutrients.